2022
DOI: 10.1136/bmjopen-2021-055822
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the impact of an enhanced recovery after surgery (ERAS) programme on the quality of recovery in patients undergoing a scheduled hysterectomy: a prospective single-centre before-after study protocol (RAACHYS study)

Abstract: IntroductionThe enhanced recovery after surgery (ERAS) programmes following hysterectomies have been studied since 2010, and their positive effects on clinical or economic criteria are now well established. However, the benefits on health outcomes, especially rapid recovery after surgery from patients’ perspective is lacking in literature, leading to develop scores supporting person-centred and value-based care such as patient-reported outcome measures. The aim of this study is to assess the impact of an ERAS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
0
6
0
1
Order By: Relevance
“…Early resumption of feeding and early mobilisation is facilitated according to our local ERAS protocol. 52 …”
Section: Methods and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Early resumption of feeding and early mobilisation is facilitated according to our local ERAS protocol. 52 …”
Section: Methods and Analysismentioning
confidence: 99%
“…This calculation was based on the following: (1) an RCT on laparoscopic colorectal cancer surgery showed that general anaesthesia combined with epidural block led to mean total QoR-15 scores of 116 (SD=4) and 123 (SD=7) on POD 3 and POD 7, respectively. 54 (2) Our ongoing Réhabilitation Améliorée Après Chirurgie pour HYSterectomie programmée (RAACHYS) study investigating the impact of an ERAS programme on patients undergoing hysterectomy 52 shows that on POD 1, the SD of the mean total QoR-15F score is 20. Therefore, for the sample size calculation, we hypothesised that the SD would be 15.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Ця схема доповнюється регіонарними методами знеболення з використанням ропівакаїну й бупівакаїну [32]. Дані препарати мають значну перспективу використання при веденні пацієнтів до, під час і після абдомінальної гістеректомії.…”
Section: огляд літературиunclassified
“…), but it still has problems such as postoperative complications and slow recovery, which requires the implementation of an accelerated functional recovery programme. [5][6][7][8] The Enhanced Recovery After Surgery (ERAS), or Fast Track Surgery, aims to minimise the physiological stress of surgery and optimise patient rehabilitation, 9 as the perioperative period generally triggers a complex cascade of pathophysiological changes in the patient's body caused by psycho-emotional, endocrine, metabolic and inflammatory reactions. 4,10,11 The published literature reports on ERAS programmes in colorectal surgery, general surgery and gynaecologic oncology surgery, which makes it difficult to evaluate the success of such programmes on the outcomes of gynaecologic surgery, although the sources reviewed indicate positive aspects in terms of shorter hospital stays, lower overall healthcare costs and increased patient satisfaction.…”
mentioning
confidence: 99%
“…Interesting findings included the composition of the prehab programme (exercise, nutrition and psychological interventions), duration and outcome measures used to determine the impact of prehab as opposed to standard care. 1,7,14,32,38 The first guideline of the Enhanced Recovery After Surgery (ERAS ® ) Society for primary and secondary hospitals in low-middle-income countries (LMICs) for elective abdominal and gynaecological care was the Guidelines for Perioperative Care in Elective Abdominal and Pelvic Surgery at Primary and Secondary Hospitals in Low-Middle-Income Countries (LMIC's): Enhanced Recovery After Surgery (ERAS) Society Recommendation. 39 An interesting finding was the literature report on certain specific perioperative complications, among which the rare one is compartment syndrome (CS) of the lower leg.…”
mentioning
confidence: 99%